(untitled) (Fiep Bulletin - online, 2011)
The purpose of this article is a warning for a type of school violence that has been studied in Brazil in recent years, called bullying. For that reason, an initial concept, the description of behavior, its inner classifications, causes and determinants. One form of violence that has come to prominence through the scholarship is bullying, especially in some countries. According to Almeida, Lisbon and Caurcel (2007), Lopes Neto (2005) and Pizarro and Jiménez (2007) such violence occurs through bullying and intimidation of a student by one or several colleagues, with the clear intention of causing him pain and presents repetitive nature and intent. Are being accessed bibliographic databases and relevant Internet pages, identifying recent articles and texts on the subject. Besides these methodological aspects are realziada fieldwork in a public school in the municipality of Rio de Janeiro, gathering data, analyzing and interpreting bullying in this space. By the time we can point to the existence of bullying in the school. When analyzing the students who resort to when mistreated at school, then you realize that most search assistance from parents and teachers. Hence the importance of teachers being exploited for peceberem, act and change this situation.